Flexural behavior of hybrid PVA fiber and AR-Glass textile reinforced geopolymer composites - Shaikh, Faiz; Patel, A. (2018)
Textile reinforced mortar or concrete, a thin cementitious composite reinforced by non-corrosive polymer textile fabric, was developed and has been researched for its role on repair and strengthening of reinforced concrete (RC) structures. Due to embedment of polymeric textile fabric inside the cementitious matrix, many researchers argued the superiority of this technology than the externally bonded fiber reinforced polymer (FRP) sheet in RC in terms of prevention of debonding of FRP and durability in fire. However, due to use of cement rich matrix the existing development of textile reinforced concrete (TRC) need to be more environmental friendly by replacing cement based binder with geopolymeric binder. This paper presents a first study on the flexural behavior of alkali resistant glass fiber textile reinforced geopolymer (TRG). In this study, two types of geopolymer binder is considered. One is fly ash based heat cured geopolymer and the other is fly ash/slag blended ambient air cured geopolymer binder. Both geopolymer types are considered in the TRG and the results are benchmarked with the current cement based TRC. The effect of short polyvinyl alcohol (PVA) fiber as hybrid reinforced with alkali-resistant (AR) glass fiber textile on the flexural behavior of above TRC and TRGs is also studied. Results show deflection hardening behavior of both TRGs with higher flexural strength in heat cured TRG and higher deflection capacity at peak load in ambient air cured TRG. The increase in PVA fiber volume fraction from 1% to 1.5% did not show any improvement in flexural strength of both TRGs although TRC showed good improvement. In the case of deflection at peak load, an opposite phenomenon is observed where the deflection at peak load in both TRGs is increased due to increase in PVA fiber volume fractions.